Urgensitas Perppu Pilkada Di Kala Wabah Pandemi Covid-19 - Rezky Panji Perdana Martua Hasibuan (ADALAH, 2020)
Abstract:The Covid-19 pandemic outbreak threatened the health of the people and affected various sectors. With this situation, several state administration agendas were also postponed, the regional head election was also not free from attention. In an effort to break the chain of distribution of Covid-19, the President called for distance and avoid activities that involved large crowds. On the basis of these considerations and with urgency, through the power of the president a policy of postponing the elections was also presented in the form of a Government Regulation in lieu of an Act as a legacy effort.Keywords: local elections, Covid-19, Perppu Abstrak:Wabah pandemi Covid-19 telah mengancam kesehatan rakyat dan berdampak kepada pelemahan berbagai sektor. Dengan keadaan ini beberapa agenda ketatanegaraan turut ditunda, pemilihan kepala daerah juga tidak lepas dari perhatian. Sebagai upaya memutus mata rantai penyebaran Covid-19, Presiden menyerukan untuk melakukan jaga jarak dan menghindari kegiatan yang melibatkan orang banyak. Atas dasar pertimbangan tersebut dan dengan keadaan mendesak, melalui kekuasaan presiden sebuah kebijakan penundaan pilkada turut dihadirkan dalam bentuk Peraturan Pemerintah Pengganti Undang-Undang sebagai upaya legasi.Kata Kunci: Pilkada, Covid-19, Perppu